Generation of green frequency comb from chirped χ(2) nonlinear photonic crystals - Lai, C.-M.; Chang, K.-H.; Yang, Z.-Y.; Fu, S.-H.; Tsai, S.-T.; Hsu, C.-W.; Yu, N. E.; Boudrioua, A.; Kung, A. H.; Peng, L.-H. (Applied physics letters, 2014)
Spectrally broad frequency comb generation over 510–555 nm range was reported on chirped quasi-phase-matching (QPM) χ(2) nonlinear photonic crystals of 12 mm length with periodicity stepwise increased from 5.9 μm to 7.1 μm. When pumped with nanosecond infrared (IR) frequency comb derived from a QPM optical parametric oscillator (OPO) and spanned over 1040 nm to 1090 nm wavelength range, the 520 nm to 545 nm up-converted green spectra were shown to consist of contributions from (a) second-harmonic generation among the signal or the idler modes, and (b) sum-frequency generation (SFG) from the neighboring pairs of the signal or the idler modes. These mechanisms led the up-converted green frequency comb to have the same mode spacing of 450 GHz as that in the IR-OPO pump comb. As the pump was further detuned from the aforementioned near-degeneracy point and moved toward the signal (1020–1040 nm) and the idler (1090–1110 nm) spectral range, the above QPM parametric processes were preserved in the chirped QPM devices to support up-converted green generation in the 510–520 nm and the 545–555 nm spectral regime. Additional 530–535 nm green spectral generation was also observed due to concurrence of multi-wavelength SFG processes between the (signal, idler) mode pairs. These mechanisms facilitate the chirped QPM device to support a single-pass up-conversion efficiency ∼10% when subject to an IR-OPO pump comb with 200 mW average power operated near- or off- the degeneracy point.